Mainframe Zero Strategy: Eliminating Legacy Dependencies through Cloud-Native Data Platforms - Naga Malleswara Babu Velpuri (International Journal of Computational and Experimental Science and Engineering, 2026)
Critical business processes in financial services, retail, healthcare, and government sectors have decades of experience and processing of significant commercial volumes of transactions on enterprise mainframe systems and have been entrusted with the custody of sensitive organizational information. Nevertheless, these old platforms create major limitations to organizational agility, integration capacities, and responsibilities to changing market requirements despite their transferable reliability and security features. Targeting both the technical change and the organizational change, governance restructuring, and the development of workforce capabilities, the Mainframe Zero (MFZ) strategy introduces a systematic approach to the systematic removal of mainframe dependencies by migrating to cloud-native data platforms. Frameworks include discovery processes to catalog the workloads and business dependencies, risk-based phasing to order activities during migration by business value and technical complexity, data migration with both bulk historical backfill and change data capture frameworks, and application refactoring with the use of strangler fig patterns to break down the project incrementally. Target-state architectures use managed cloud databases, such as BigQuery to support analytics workloads, Cloud Spanner to support transactions where the world is one, and event-driven messaging infrastructure to replace batch-based processing models. Security and compliance integration integrates identity management, encryption, network controls, and monitoring features in line with the NIST Cybersecurity Framework across the execution of transformation. Organizational enablement focuses on domain-related team architecture, platform engineering competencies, federated governance frameworks, and communication mechanisms that maintain stakeholder trust in the course of long-term move programs. An example of a case study has shown quantifiable results such as cost reduction of infrastructures by eradicating mainframe licensing, better recovery targets by utilization of multi-region deployment structures, and higher velocity of feature delivery by contemporary development methods. Decision frameworks help technology leaders to choose the suitable migration patterns in terms of workload characteristics, strategic goals, and risk tolerance, and prioritize the transformation domains and control the risk accordingly during cloud-native modernization programs.